Hidden treasure: a study of unclaimed property management by state government. Issue 1 (5th March 2018) - Wilson, Darrin; Slagle, Derek
Abstract : Purpose: Unclaimed property is an important part of state government operations, yet very little research has been conducted on the function of returning unclaimed property to owners or the related public administration operation of unclaimed property. The purpose of this paper is to offer an exploratory study of unclaimed property in the USA and the factors that influence management. Design/methodology/approach: The authors use Agency Theory to examine the role of unclaimed property in state government budgeting and operations. The data consisted of a 2011 survey of state unclaimed property agencies, which was utilized for a regression model. Findings: Results showed: type of uniform code used to govern unclaimed property; and presence and size of marketing staff in the agency had a significant relationship with extent of property returned to owners. Originality/value: This is the first comprehensive study on how state governments manage unclaimed property. This study can provide practitioners, policymakers, and researchers with a better insight into unclaimed property management.